If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4(x + -3) = 3x + -12 Reorder the terms: 3 + -4(-3 + x) = 3x + -12 3 + (-3 * -4 + x * -4) = 3x + -12 3 + (12 + -4x) = 3x + -12 Combine like terms: 3 + 12 = 15 15 + -4x = 3x + -12 Reorder the terms: 15 + -4x = -12 + 3x Solving 15 + -4x = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + -4x + -3x = -12 + 3x + -3x Combine like terms: -4x + -3x = -7x 15 + -7x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -7x = -12 + 0 15 + -7x = -12 Add '-15' to each side of the equation. 15 + -15 + -7x = -12 + -15 Combine like terms: 15 + -15 = 0 0 + -7x = -12 + -15 -7x = -12 + -15 Combine like terms: -12 + -15 = -27 -7x = -27 Divide each side by '-7'. x = 3.857142857 Simplifying x = 3.857142857
| 3(6+6x)=234 | | 8x+5y=1600 | | 30=x+.06x | | f(x)=300x-5x^2-5 | | F(0)=4x^2-9x+8 | | -40-(-53)= | | =300x-5x^2-5 | | 2a^4-5a^3-2a^2+10a-4=0 | | 2(x-7)+x=11 | | 5-x+2x-29=4x-34 | | (6*x)/2-6*5=(6*x)/3 | | 2(10+5x)=50 | | 29-3b+b^2=0 | | 7-6(x-5)=2x-9 | | M-[2-(2-m)]= | | 3x+7=3(x+8) | | a^4+2a^2-63=0 | | 7(1+2x)=161 | | 1-9B^2= | | -3s-10+s^2=0 | | 1000+5000x=12000 | | 5-5x=-4x+2 | | a^3-4a^2-45a=0 | | 6x+3=6(x+2) | | 2.5x=4.8 | | 9-7(x-2)=4x-13 | | Y=(x-5)(x-1) | | log(4x+1)=0 | | 4x=26-4 | | 5(8x+2)=-26 | | v^2+v+30=0 | | 5x+2x-29=4x+34 |